2011
DOI: 10.1177/0022343311417981
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to trust? Institutional capacity, conflict, and political trust in Africa, 2000–2005

Abstract: Civil conflict and state failure has often been linked to breakdowns in regime legitimacy. Trust in government is a critical element of regime legitimacy and the state's ability to mediate between the demands of competing groups within society. We contend that government capability is a primary factor in shaping individuals' ascription of legitimacy to the state. Capable governments foster perceptions of legitimacy while poor institutional performance decreases the degree to which individuals trust their gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 40 publications
2
96
2
2
Order By: Relevance
“…Cassar, Grosjean, and Whitt (2013), Cuesta and Alda (2012), Luca and Verpoorten (2015), and Rohner, Thoenig, and Zilibotti (2013), yet there is only a handful of studies devoted to the topic of trust in government. These studies found that satisfaction with government services is a strong predictor of trust in government (Askvik, Jamil, and Dhakal, 2011;Hutchison and Johnson, 2011;Sacks and Larizza, 2012;Stoyan et al, 2016), a finding consistent with studies in developed countries.…”
Section: P O L I T I C a L T R U S T A N D S Tat E B U I L D I N Gsupporting
confidence: 86%
See 2 more Smart Citations
“…Cassar, Grosjean, and Whitt (2013), Cuesta and Alda (2012), Luca and Verpoorten (2015), and Rohner, Thoenig, and Zilibotti (2013), yet there is only a handful of studies devoted to the topic of trust in government. These studies found that satisfaction with government services is a strong predictor of trust in government (Askvik, Jamil, and Dhakal, 2011;Hutchison and Johnson, 2011;Sacks and Larizza, 2012;Stoyan et al, 2016), a finding consistent with studies in developed countries.…”
Section: P O L I T I C a L T R U S T A N D S Tat E B U I L D I N Gsupporting
confidence: 86%
“…When a government dutifully performs its functions, it is considered as legitimate. Therefore, it is argued, improvements in public services should induce citizens' confidence in government (Hutchison and Johnson, 2011). Further to the argument, Sacks and Larizza (2012) highlighted the behavioral mechanism that underlies this exchange relationship.…”
Section: Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…48 World Bank Conflict Prevention and Reconstruction Unit 2002, 3. 49 Askvik, Jamil, and Nath Dhakal 2011;Coleman 1994;Dasgupta 1988;Hetherington 1998;Hutchison and Johnson 2011;Levi 1998;Rotberg 2004; Van de Walle and Bouckaert 2003. demonstration that the state will consistently meet its commitments and uphold a high standard of behavior, is one of the most fundamental determinants of trust. 50 Similarly, Raiser argues that the state can build trust by exercising moral leadership.…”
Section: Institutional Theoriesmentioning
confidence: 99%
“…17 Askvik, Jamil, and Nath Dhakal 2011. 18 Hutchison andJohnson 2011. 19 Azar 1990;Coleman 2003;Crocker, Hampson, and Aall 2005.…”
Section: Introductionmentioning
confidence: 99%